Integration of Humidity Sensors into Fibre-reinforced Thermoplastic Composites. (2016) - Ebert, F.; Seider, T.; Illing-Günther, H.; Nendel, K.; Martin, J.; Otto, T.; Gessner, T.; Nestler, D.; Wagner, G.
Abstract: Due to the functional integration and weight reduction lightweight structures are more and more important, e.g. for automotive, boat or aircraft engineering. Integration of sensors in composites gives information about different mechanical stresses and conditions (failure, impact etc). Furthermore, environmental conditions have a significant influence on operation and durability, e.g. temperature and humidity. Due to the importance of these parameters, this contribution deals with the detection of moisture in composites. The developed foil-based humidity sensors were placed on foil tapes by means of stitching and integrated into fibre-reinforced thermoplastic composites.